"Такі свої чужіші чужини" (виражальні можливості морфологічних категорій у романі Ліни Костенко "Берестечко") - Дільна, О. (Культура слова, 2020)
У статті проаналізовано стилістичну роль слів різних частин мови (іменників, прикметників, займенників, дієслів) у романі Ліни Костенко «Берестечко». Розкрито виражальні можливості граматичних анормативів, ужитих у тексті роману. Описано прийом переносного вживання однієї морфологічної форми замість іншої (однина іменника замість множини і навпаки, взаємозаміна займенників одного розряду, часових, особових і способових форм дієслова) і спричинену цим явищем зміну змісту висловлювання. The article analyzes the expressive possibilities of the words belonging to different parts of speech (nouns, adjectives, pronouns, verbs) in Lina Kostenko’s novel «Berestechko». The main focusis on the stylistic role of grammatical non-normatives used in the text of the novel in question: non-standard forms of the number of nouns, irregular forms of comparative degrees of adjectives and non-normative pronouns. Such forms are evaluated according to the norms of the literary language regarding their semantics and stylistics hades of meaning (solemnity, familiarity, diminutive form, intimacy, colloquialism, etc.) given to the utterance. There is a detailed description of the metaphoricuse of one morphological form instead of another: singular form of noun instead of plural and viceversa, one pronoun instead of the other one, one tense form and mood of the verb instead of another. The article emphasizes the technique of nounstring (the same noun in different cases and pronouns of different categories). Stylistic aim of metaphoric form usageis clarified; the description is provided how the meaning of the utteranceis changed, what stylistic shades of meaning appearine very separate case and how they influence the communicative aim of the utterance.